2017
DOI: 10.5606/archrheumatol.2017.6212
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Axial Spondyloarthritis is Associated With Higher Disease Activity

Abstract: Objectives: This study aims to assess whether vitamin D deficiency is associated with increased disease activity and functional impairment in axial spondyloarthritis (axSpA), with control for its seasonal variation. Patients and methods: Serum 25-hydroxyvitamin D [25(OH)D] levels were measured in 235 consecutive axSpA patients (176 males, 59 females; mean age 46.3 years; range 18 to 85 years) attending a specialist spondyloarthritis service in the United Kingdom. Disease activity and functional status were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Our results are contrary to data from other studies that reported a significant association between vitamin D and activity of SpA as well as structural damage [1, 3, 4]. However, differences in the study population and in the definition of vitamin deficiency do not allow direct comparison of these results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are contrary to data from other studies that reported a significant association between vitamin D and activity of SpA as well as structural damage [1, 3, 4]. However, differences in the study population and in the definition of vitamin deficiency do not allow direct comparison of these results.…”
Section: Discussioncontrasting
confidence: 99%
“…Deficiency of vitamin D is frequent in patients with spondyloarthritis (SpA) [1, 2] and some data suggest its association with increased disease activity and structural damage [3, 4]. Apart from the endocrine role in bone metabolism by maintaining mineral homeostasis, vitamin D 3 can modulate both innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current evidences deriving from systematic reviews and meta-analysis suggest that AS patients harbor lower vitamin D values than controls [71,72]. However, whether an association links vitamin D status to disease activity is debated, with some papers demonstrating an inverse association between 25(OH)D3 and disease activity [73,74] and others refusing this finding [75,76]. Currently, there are no trials investigating the effect of vitamin D supplementation on disease activity.…”
Section: Spondyloarthritismentioning
confidence: 99%
“…46 But a crosssectional study by Zhao et al, which demonstrated an association between vitamin D deficiency and both higher disease activity and functional impairment in axial SpA, supports the hypothesis that vitamin D has an immunomodulatory role. 47 A study conducted on Chinese patients showed a significantly lower vitamin D levels in Chinese axial SpA patients as compared to the control group.…”
mentioning
confidence: 99%